Electrical Activity of Extended Defects in Relaxed InxGa1−xAs Hetero-Epitaxial Layers. (19th February 2020) - Claeys, C.; Hsu, P.-C.; Mols, Y.; Han, H.; Bender, H.; Seidel, F.; Carolan, P.; Merckling, C.; Alian, A.; Waldron, N.; Eneman, G.; Collaert, N.; et al.
Abstract : The electrical activity of extended defects in III–V materials, combining different analysis methods based on lifetime extraction from diode current-voltage characteristics, time resolved photoluminescence (TRPL) and deep level studies using Deep Level Transient Spectroscopy (DLTS) is reviewed. To that purpose p + n junction diodes have been fabricated in In0.53 Ga0.47 As hetero-epitaxial layers on semi-insulating InP or GaAs substrates. By depositing a strained buffer layer, the Extended Defect Density (EDD) can be varied over several decades, enabling a systematic study of their electrical impact in the same range. The defect densities are determined by High-Resolution X-ray Diffraction (HR-XRD), DLTS and Electron Channeling Contrast (ECCI) techniques. The generation and recombination (GR) lifetimes of the In0.53 Ga0.47 As layers become dominated by the EDs for densities above about 3 × 10 7 cm −2, whereby the dominant GR level moves closer to the mid gap position. This is supported by DLTS investigations, showing the occurrence of specific electron traps for defective epi layers, which exhibit a capture behavior that is typical for extended defects.